SISTEM INFORMASI REKAM MEDIK PADA RUMAH SAKIT BERSALIN GRAHA RAP TANJUNG BALAI KARIMUN - Endang Lestari Ruskan; Ken Ditha Tania; Lailatur Rahmi (Jurnal Sistem Informasi, 2011)
for to explain how to design and build a medical record information system at Graha Rap maternity hospital in Tanjung Balai Karimun. The problem is medical record system is still used manual which is written on the paper by the receptionist. Disanvantages of using the system is taking long enough time to find the data of patients, it often data redundancies and alsoÂ  patient card loss. Data requiredÂ  is collected by observasing and some dataÂ  That is obtained from Graha RapÂ  maternity hospital in tanjung Balai Karimun. FAST method is used to do system development. The result of this final task are â€œA MEDICAL RECORD INFORMATION SYSTEM AT GRAHA RAP IN TANJUNG BALAI KARIMUNâ€ that is computerizedÂ  with this new system will speed ip processing the whole patients documents at Graha Rap maternity hospital and also to overcome the data redundancies, medical record card loss that will reduce error. The result is also speed up processing the patients data. Â  Key word: Rekam medik, Sistem Informasi, rumah sakit, FAST.